(Un)Preparing a Revolution: The Comintern in the Prelude to the 1926–1927 Uprisings in Indonesia - Kankan Xie (The Russian Revolution in Asia: From Baku to Batavia, 2021)
This chapter assesses the 1926-1927 Uprising in Indonesia across several interconnected geographic and institutional scales: In the Comintern, where exiled leaders of the Partai Komunis Indonesia conferred with Comintern representatives about the situation at home; in the highest levels of the Politburo, where disagreements over revolutionary tactics in China exacerbated the power struggle between Stalin and Trotsky; and in Indonesia itself, where colonial repression inspired the abortive uprising. In so doing, this chapter shows how the Uprising demonstrated the limits of internationalism. As PKI leaders were unable to maintain effective contact with the movement in Indonesia, gaps in information undermined decision-making and led to conflict over the applicability of Russian models to the Indonesian context. Debates over Moscow’s China policy diverted attention from other territories and drew PKI members into the Stalin-Trotsky feud. Comintern support for the Uprising, therefore, did not materialize, further undermining the communist movement in Indonesia.